Phenotypic whole-cell screening identifies a protective carbohydrate epitope on Klebsiella pneumoniae. Issue 1 (31st December 2022) - Berry, Sophia K.; Rust, Steven; Caceres, Carolina; Irving, Lorraine; Bartholdson Scott, Josefin; Tabor, David E.; Dougan, Gordon; Christie, Graham; Warrener, Paul; Minter, Ralph; Grant, Andrew J.
ABSTRACT: The increasing global occurrence of recalcitrant multi-drug resistant Klebsiella pneumoniae infections warrants the investigation of alternative therapy options, such as the use of monoclonal antibodies (mAbs). We used a target-agnostic phage display approach to K. pneumoniae bacteria lacking bulky, highly variable surface polysaccharides in order to isolate antibodies targeting conserved epitopes among clinically relevant strains. One antibody population contained a high proportion of unique carbohydrate binders, and biolayer interferometry revealed these antibodies bound to lipopolysaccharide (LPS). Antibodies that bound to O1 and O1/O2 LPS were identified. Antibodies were found to promote opsonophagocytic killing by human monocyte-derived macrophages and clearance of macrophage-associated bacteria when assessed using high-content imaging. One antibody, B39, was found to protect mice in a lethal model of K. pneumoniae pneumonia against both O1 and O2 strains when dosed therapeutically. High-content imaging, western blotting and fluorescence-activated cell sorting were used to determine binding to a collection of clinical K. pneumoniae O1 and O2 strains. The data suggests B39 binds to D-galactan-I and D-galactan-II of the LPS of O1 and O2 strains. Thus, we have discovered an mAb with novel binding and functional activity properties that is a promising candidate for development as a novel biotherapeutic for the treatment and prevention of K. pneumoniae infections.